2017
DOI: 10.1038/srep45779
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound (LIPUS) prevents periprosthetic inflammatory loosening through FBXL2-TRAF6 ubiquitination pathway

Abstract: Previous studies have shown that Low intensity pulsed ultrasound(LIPUS) prevents polyethylene-debris-induced periprosthetic loosening in vivo, but the details of the mechanism by which it does so remain unclear. In this article, we used polyethylene debris induced RAW 264.7 cells as the in vitro model, and tested the effect of LIPUS on this model. Changes in the level of inflammatory cytokines, cell proliferation, and apoptosis were assessed. Gene overexpression and siRNA technique were applied, and the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…We previously reported to this extent that LIPUS stimulation inhibits Toll‐like receptor 4‐myeloid differentiation primary response gene 88 (MyD88) complex formation . Other reports have also shown that LIPUS downregulates the protein expression levels of IL‐1β receptor, and TNF receptor associated factor 6 . In the present study, we found that ROCK1, a molecule majorly involved in cytoskeletal rearrangements following activation by Rho, was critically involved in the suppressive effects of LIPUS on inflammatory reactions (Figure ).…”
Section: Discussionsupporting
confidence: 68%
“…We previously reported to this extent that LIPUS stimulation inhibits Toll‐like receptor 4‐myeloid differentiation primary response gene 88 (MyD88) complex formation . Other reports have also shown that LIPUS downregulates the protein expression levels of IL‐1β receptor, and TNF receptor associated factor 6 . In the present study, we found that ROCK1, a molecule majorly involved in cytoskeletal rearrangements following activation by Rho, was critically involved in the suppressive effects of LIPUS on inflammatory reactions (Figure ).…”
Section: Discussionsupporting
confidence: 68%
“…The number of regenerated axons, the mean diameter of the regenerated axons, and the thickness of the myelin sheath on these axons were all significantly different from the corresponding values in SN-SC group. Additionally, Masson's trichrome staining and electrophysiological analyses are widely accepted techniques for functionally evaluating sciatic nerve repair 41 , 42 . The results obtained in the Fb&SC group were preferable to those obtained in the SN-SC group with regard for functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS has been recently reported to have biologic relevance in the context of inflammation. LIPUS treatment was shown to alleviate the lipopolysaccharide-induced inflammatory response in murine RAW264.7 macrophages by increasing the activation of caveolin-1 [ 95 ], and also improved the general status of coxsackievirus-B3-infected mice including their ventricular function by suppressing CD68+ infiltration in the heart [ 96 , 97 ]. Related to inflammation, LIPUS was found to inhibit the inflammatory pathways activated during aseptic joint loosening [ 97 ], suggesting an anti-inflammatory role for LIPUS in the orthopedic context.…”
Section: Biological Effects Of Ultrasoundmentioning
confidence: 99%
“…LIPUS treatment was shown to alleviate the lipopolysaccharide-induced inflammatory response in murine RAW264.7 macrophages by increasing the activation of caveolin-1 [ 95 ], and also improved the general status of coxsackievirus-B3-infected mice including their ventricular function by suppressing CD68+ infiltration in the heart [ 96 , 97 ]. Related to inflammation, LIPUS was found to inhibit the inflammatory pathways activated during aseptic joint loosening [ 97 ], suggesting an anti-inflammatory role for LIPUS in the orthopedic context. In a similar line, LIPUS was shown to inhibit the production of mature IL1β in a murine model of synovial inflammation [ 98 ], and to reduce histological damage and lesion size in the joints of mice with systemic autoimmunity [ 99 ].…”
Section: Biological Effects Of Ultrasoundmentioning
confidence: 99%